Trial strategy and techniques in highway contract litigation. - National Cooperative Highway Research Program; National Research Council (U.S.). Transportation Research Board (Washington, D.C. Transportation Research Board, 1979)
"A report submitted under ongoing NCHRP Project 20-6, "Right-of-Way and Legal Problems Arising Out of Highway Programs," for which the Transportation Research Board is the agency conducting the research."
Caption title.
At head of title: National Cooperative Highway Research Program.
March 1979.
Keywords: Highway research -- United States